Wage setting, taxes and demand for labour: Multivariate analysis of the cointegration relations - Timo Tyrväinen (Bank of Finland, 1992)
As an outcome of modelling wage setting and demand for labour in a bargaining framework, a lO-dimensional vector space is defined. This overparametrized system is reduced by means of conditioning. Structural restrictions which identify the long-run relations of interest are specified. The restrictions which characterize wage setting and labour demand schedules are imposed and tested first separately and then jointly.
URN:NBN:fi:bof-201808021857
Keywords: 330